2011
DOI: 10.1177/1759720x11416862
|View full text |Cite
|
Sign up to set email alerts
|

Improved sleep efficiency after anti-tumor necrosis factor α therapy in rheumatoid arthritis patients

Abstract: Abstract:Background: Poor sleep health is increasingly recognized as contributing to decreased quality of life, increased morbidity/mortality and heightened pain perception. Our purpose in this study was to observe the effect on sleep parameters, specifically sleep efficiency, in rheumatoid arthritis (RA) patients treated with anti-tumor necrosis factor alpha (anti-TNF-a) therapy. Methods: This was a prospective observational study of RA patients with hypersomnolence/ poor sleep quality as defined by the Epwor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
24
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 39 publications
5
24
2
1
Order By: Relevance
“…In this work, greater severity of the SAHS is observed in patients with inflammatory arthritis as well as its improvement, evaluated through the AHI, with treatment with anti-TNF-α. This corroborates some preliminary observation [12] and the importance that these drugs may have as modulators of the common etiopathogenic nexus of inflammatory arthritides with associated SAHS.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this work, greater severity of the SAHS is observed in patients with inflammatory arthritis as well as its improvement, evaluated through the AHI, with treatment with anti-TNF-α. This corroborates some preliminary observation [12] and the importance that these drugs may have as modulators of the common etiopathogenic nexus of inflammatory arthritides with associated SAHS.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, when SAHS is treated with continuing positive air pressure, a reduction is observed in blood pressure, triglycerides and glycated hemoglobin [11]. Furthermore, it has been stated that treatment with anti-TNF-α in patients with RA and sleep disorders improves sleep quality [12]. However, at present, there are still few studies that evaluate the severity of SAHS in patients with RA or SpA, the increase of CV risk that this association implies and the possible modulation of the nighttime anoxia-hypoxia episodes with treatment with anti TNF-α drugs.…”
Section: Introductionmentioning
confidence: 99%
“…3,30 The study by Taylor-Gjevre et al 31 demonstrated improved sleep efficiency and "awakening after sleep onset" time observed by polysomnography in RA patients treated with anti-tumor necrosis factor-alpha therapy. However, the mean PSQI scores increased (10.4 to 10.8) with the therapy despite significant reduction in the disease activity (p=0.048).…”
Section: Discussionmentioning
confidence: 98%
“…This TNF-α (-308) allele has been described as significantly associated with a diagnosis of OSA compared with population controls [17]. Anti-TNF-α biologic strategies have been reported to have some efficacy in treatment of OSA patients (without concurrent rheumatic disease) and also on some polysomnographic sleep parameters in RA patients [18,19]. A lower incidence of OSA in ankylosing spondylitis patients on anti-TNF-α therapies has been observed [20].…”
mentioning
confidence: 94%